2002
DOI: 10.1162/089892902317362010
|View full text |Cite
|
Sign up to set email alerts
|

An fMRI Study on the Time-Limited Role of the Medial Temporal Lobe in Long-Term Topographical Autobiographic Memory

Abstract: The time-limited role of the medial temporal lobe (MTL) in human long-term memory is well known. However, there is still no direct neuroimaging evidence to confirm it. In this fMRI study, nine subjects were scanned while asked to recall the places they visited more than seven years ago (remote memories); and the places they visited recently (recent memories). We observed robust and dominant MTL activity peaking in the left parahippocampal gyrus when recent memories were contrasted with remote memories. This re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
80
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(91 citation statements)
references
References 20 publications
10
80
1
Order By: Relevance
“…SCM predicts greater hippocampal activity for recent than remote AMs (i.e., a remoteness effect), whereas MTT predicts that if both types of AMs are equally detailed and vivid, they should elicit similar hippocampal activity (i.e., no remoteness effect). Although a few functional neuroimaging studies found the remoteness effect predicted by SCM (Niki & Luo, 2002;Piefke, et al, 2003) most of the studies comparing remote and recent AMs did not, supporting MTT Conway, et al, 1999;Gilboa, et al, 2004;Maguire & Frith, 2003b;Maguire, et al, 2001;Piolino et al, 2004;Rekkas & Constable, 2005;Ryan, et al, 2001;Viard et al, 2007) and consistent with emerging evidence in the patient literature, which suggests that MTL damage can impact remote AMs greater than was previously found (Steinvorth, et al, 2005). However, neuroimaging evidence cannot irrefutably determine the necessity of the hippocampus in the retrieval of remote AMs.…”
Section: Remote Autobiographical Memoriessupporting
confidence: 55%
See 1 more Smart Citation
“…SCM predicts greater hippocampal activity for recent than remote AMs (i.e., a remoteness effect), whereas MTT predicts that if both types of AMs are equally detailed and vivid, they should elicit similar hippocampal activity (i.e., no remoteness effect). Although a few functional neuroimaging studies found the remoteness effect predicted by SCM (Niki & Luo, 2002;Piefke, et al, 2003) most of the studies comparing remote and recent AMs did not, supporting MTT Conway, et al, 1999;Gilboa, et al, 2004;Maguire & Frith, 2003b;Maguire, et al, 2001;Piolino et al, 2004;Rekkas & Constable, 2005;Ryan, et al, 2001;Viard et al, 2007) and consistent with emerging evidence in the patient literature, which suggests that MTL damage can impact remote AMs greater than was previously found (Steinvorth, et al, 2005). However, neuroimaging evidence cannot irrefutably determine the necessity of the hippocampus in the retrieval of remote AMs.…”
Section: Remote Autobiographical Memoriessupporting
confidence: 55%
“…Moreover, there is evidence that different PFC regions are activated depending on the age of the AMs (Niki & Luo, 2002;Rekkas & Constable, 2005).…”
Section: Age Of the Participants Investigating The Neural Correlatesmentioning
confidence: 99%
“…The remaining six papers discussed by Maguire (2001), plus two other recent papers (Markowitsch et al, 2000;Niki & Luo, 2002), have addressed two main issues with respect to the neural basis of autobiographicalmemory: (1) whether some regions of the brain, especially the hippocampus and other medial temporal lobe regions, are more involved in the retrieval of recent memories (Conway et al, 1999;Maguire, Henson, Mummery, & Frith, 2001;Niki & Luo, 2002;Ryan et al, 2001), and (2) the role played by more lateral temporal and frontal regions in the retrieval of personal events (Conway et al, 1999;Fink et al, 1996;Maguire & Mummery, 1999;Maguire et al, 2000;Markowitsch et al, 2000). Until Niki and Luo, there was relatively little evidence that hippocampal regions were more active during the retrieval of recent in comparison with remote memories (see Murre, Graham, & Hodges, 2001;Nadel, Samsonovich, Ryan, & Moscovitch, 2000;Nestor, Graham, Bozeat, Simons, & Hodges, 2002;Squire, 1992, for theoretical reviews about this issue).…”
Section: Functional Neuroimaging Studies Of Autobiographical Memorymentioning
confidence: 99%
“…On the one hand, several recent functional activation studies in healthy volunteers have provided evidence that the hippocampus and related medial temporal lobe structures are more activated during the retrieval of recent compared with remote episodic memories (Haist et al 2001;Niki and Luo 2002;Piefke et al 2003;Mayes et al 2004). These investigations have used autobiographical or famous faces tasks, and the findings could be interpreted as consistent with consolidation theory.…”
mentioning
confidence: 99%